Induction of T cell adhesion by antigen stimulation and modulation by the coreceptor CD4. - Michel, F; Acuto, O (1996)
T cell adhesion induced after physiological stimulation by antigen was investigated using murine T cell hybridomas specific for a tetanus toxin peptide. By employing a novel assay, the T cell hybridomas were shown to strongly adhere to peptide-pulsed APC in a dose-dependent fashion. Adhesion peaked at 30-60 min and declined thereafter. This assay allowed us to study the relationship between T cell adhesion and later activation responses using tetanus toxin peptide and alanine monosubstituted analogs. We show that the degree of peptide-induced T cell adhesion correlated with the magnitude of late functional responses. CD4, LFA-1 (CD11a/CD18), and CD28 were critical in the adhesion response. The enhancing role of CD4 was further demonstrated by reduced levels of T cell adhesion and late responses of CD4- T cell hybridomas. Reexpression of CD4 reversed these defects. Our data suggest a link between antigen-induced T cell adhesion and late responses and also suggest that signals mediated by TCR and CD4 coengagement may induce a greater activation and/or recruitment of molecules involved in T cell adhesion.